Polishing powder for last polishing of optical glass as well as preparation method and application of polishing powder
By using dispersant surfactants and reducing agents to regulate the process of preparing cerium oxide polishing powder, the problem of uneven particle size in existing cerium oxide polishing powders has been solved, and cerium oxide polishing powders with high specific surface area and small grain size have been prepared, thereby improving the polishing performance and lifespan of optical glass.
Patent Information
- Application Number
- CN202510838423.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-11-07
AI Technical Summary
Existing technologies make it difficult to prepare cerium oxide polishing powder with high specific surface area and small grain size, resulting in poor final polishing effect and insufficient polishing life of optical glass.
Cerium oxide polishing powder was prepared by using a method that regulates the reaction conditions by adding a dispersant surfactant and a reducing agent to a precipitant solution. This method controls the reaction conditions to obtain uniform cerium oxide polishing powder with small grains.
Cerium oxide polishing powder with high specific surface area and small grain size was prepared, which improved the polishing effect and polishing life of optical glass.
Smart Images

Figure CN120904791A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the polishing technical field, especially to the final polishing of optical glass, in particular to a polishing powder for the final polishing of optical glass and a preparation method and application thereof. BACKGROUND
[0002] Cerium oxide is an important rare earth oxide, which has excellent catalytic performance and polishing performance, and is widely used in catalysts, polishing materials, ultraviolet absorption, special glass and other fields. Especially, cerium oxide with high specific surface area and small grain size has great advantages in the final polishing of optical glass. It not only has high chemical activity, but also can improve the wear resistance of cerium oxide abrasive, thereby improving the grinding capacity and grinding life of the polishing material.
[0003] At present, cerium oxide is obtained by calcining cerium carbonate or cerium hydroxide. In order to make the performance of cerium oxide more excellent, cerium hydroxide is usually used as a precursor for calcination. Cerium hydroxide is mainly prepared by chemical precipitation method: cerium liquid is prepared in advance, and a precipitating agent is added under oxidation conditions for precipitation to obtain cerium hydroxide. This traditional preparation method will cause poor dispersion of the liquid during preparation, and the precipitation is not uniform, resulting in uneven particle size and large morphology difference of the obtained material. It is difficult to obtain cerium oxide with high specific surface area and small grain size. SUMMARY
[0004] Therefore, in order to overcome the defects of the prior art, the purpose of the present application is to provide a preparation method of a polishing powder for the final polishing of optical glass, which can obtain cerium oxide polishing powder with high specific surface area and small grain size, and has good polishing performance and long polishing life.
[0005] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows:
[0006] The present application provides a preparation method of a polishing powder for the final polishing of optical glass, comprising the following steps:
[0007] A dispersing surfactant is added to the cerium nitrate solution, and stirred uniformly to obtain a first liquid; the dispersing surfactant is obtained by mixing polyethylene glycol and polyvinylpyrrolidone;
[0008] A premix solution is prepared, and an oxidizing agent and the premix solution are simultaneously added to the first liquid at a first temperature, and the pH value of the system is maintained at 2.0-5.0, and the oxidizing agent is added first until the premix solution is added, to obtain a second liquid; the premix solution is a mixture of a precipitating agent and a reducing agent;
[0009] The premix solution is continuously added to the second liquid at the first temperature, and the pH value of the system is maintained at 5.0-8.0;
[0010] After the premixing solution is added, the temperature is raised to the second temperature and kept, the reaction is carried out, after the reaction is completed, the temperature is lowered to the first temperature, and then the pretreated material is obtained through filtration and drying; wherein the pretreated material is cerium hydroxide;
[0011] The pretreated material is crushed to D50 of 5-50 μm, and then calcined to obtain the polishing powder. D50 refers to the particle size corresponding to 50% of the cumulative particle size distribution percentage of a sample.
[0012] The polishing process generally includes rough polishing, medium polishing and fine polishing, and the last polishing is equivalent to the fine polishing process in the polishing process, and the last polishing has the highest requirement for the surface quality of the polishing powder, and the cerium oxide polishing powder with high specific surface area and small grains has a very good advantage in the last polishing. The cerium nitrate solution is fully dispersed by the dispersing surfactant in advance, so that it can uniformly nucleate in the subsequent reaction process, and the reducing agent is added in the precipitant to prepare a premixing solution, the reducing property and the property of generating gas by decomposition of the reducing agent are used for control, so that the cerium oxide polishing powder with high specific surface area and small grains required for the last polishing of optical glass is obtained, and the polishing performance is stable and continuous. The cerium oxide polishing powder prepared in the present application has high activity, which is beneficial to enhancing the chemical corrosion and softening effect; at the same time, the small grain cerium oxide with polyhedron and edges and corners can ensure high physical grinding effect, which is more beneficial to application in the last polishing.
[0013] According to some preferred embodiments of the present application, the concentration of the cerium nitrate solution is 20-120 g / L, and the cerium nitrate solution is prepared from a cerium source and nitric acid, and the cerium source is one or a combination of cerium carbonate or cerium chloride.
[0014] According to some preferred embodiments of the present application, the mass ratio of polyethylene glycol to polyvinylpyrrolidone in the dispersing surfactant is 1:1-5. In some embodiments of the present application, the polyethylene glycol is one or a combination of PEG2000 or PEG4000, and the polyvinylpyrrolidone is one or a combination of PVP K17 or PVP K30. In the present application, polyethylene glycol and polyvinylpyrrolidone are used to prepare the dispersing surfactant for fully dispersing the cerium nitrate solution, so that it can fully and uniformly react in the reaction process, which is beneficial to obtaining finer and more uniform grains. Polyethylene glycol and polyvinylpyrrolidone are both non-ionic and not easy to decompose, and their combination can have a synergistic effect, which can effectively control the growth of cerium oxide particles and make the particles more uniform. In addition, it is also helpful to form a specific nanostructure.
[0015] According to some preferred embodiments of the present application, the percentage of the mass of the dispersing surfactant in the first feed liquid to the mass of the cerium source is 0.01-0.5%.
[0016] According to some preferred embodiments of the present application, the method for preparing the premixed solution is to first prepare a precipitant with a concentration of 5-40g / L, then add a reducing agent to the precipitant, and stir for 10-30min at a rotation speed of 300-800r / min. In some embodiments of the present application, adding the reducing agent to the precipitant can take advantage of the reducing property of the reducing agent and the property of the gas (nitrogen and ammonia) generated by the decomposition of the reducing agent, which is conducive to obtaining small grains with high specific surface area subsequently.
[0017] According to some preferred embodiments of the present application, the mass concentration of the reducing agent is 40%-60%, and the percentage of the mass of the reducing agent to the mass of the cerium source is 0.01%-0.2%.
[0018] According to some preferred embodiments of the present application, the reducing agent is one or a combination of hydrazine, hydrazine hydrate or hydrazine salt.
[0019] According to some preferred embodiments of the present application, the ratio of the amount of substance of the precipitant to the amount of substance of the cerium source is 1.1-1.8:1.
[0020] According to some preferred embodiments of the present application, the mass concentration of the oxidizing agent is 15%-35%, and the ratio of the amount of substance of the oxidizing agent to the amount of substance of the cerium source is 1.1-1.5:1.
[0021] According to some preferred embodiments of the present application, the first temperature is 30-50℃, and the second temperature is 80-100℃.
[0022] According to some preferred embodiments of the present application, after the reaction is completed and the temperature is lowered to the first temperature, the upper reaction supernatant in the reaction system is removed before filtration, and then the filtration is performed; during the filtration, the filter cake is obtained after washing with water multiple times and testing the conductivity of the filtrate after each washing until the conductivity of the filtrate reaches below 100μs / cm. Requiring the conductivity of the filtrate to be below 100μs / cm helps to remove impurity ions on the surface of cerium oxide and improve the purity.
[0023] According to some preferred embodiments of the present application, before the drying step, the filter cake obtained by filtration is crushed and then dried, and the drying temperature is 60-100℃ and the drying time is 10-30h. Crushing the filter cake before drying can ensure that the pretreated material is dried more thoroughly and uniformly.
[0024] According to some preferred embodiments of the present application, the process of simultaneously adding the oxidizing agent and the premix to the first feed liquid at the first temperature is carried out while stirring, and the stirring speed is 30-200 r / min.
[0025] According to some preferred embodiments of the present application, the process of heating to the second temperature and maintaining the temperature after the premix is added is carried out for 20-100 min.
[0026] According to some preferred embodiments of the present application, the calcination temperature is 300-800℃, and the calcination time is 1-8 h.
[0027] Preferably, the method for preparing the polishing powder for polishing optical glass according to the present application comprises the following steps:
[0028] (1) An appropriate amount of cerium source is taken and an appropriate amount of nitric acid is added to dissolve it, to prepare a cerium nitrate solution with a concentration of 20-120 g / L. An appropriate amount of polyethylene glycol and polyvinylpyrrolidone is added to water and stirred at a speed of 300-1000 r / min for 10-60 min to fully dissolve and uniformly mix the two, to obtain a dispersing surfactant. Then the dispersing surfactant is added to the cerium nitrate solution while stirring, and mixed uniformly to obtain a first feed liquid. The mass ratio of polyethylene glycol to polyvinylpyrrolidone in the dispersing surfactant is 1:1-5, and the mass percentage of the dispersing surfactant in the first feed liquid is 0.01-0.5% of the mass of the cerium source.
[0029] (2) An oxidizing agent with a mass concentration of 15%-35%, a precipitant with a concentration of 5-40 g / L, and a reducing agent with a mass concentration of 40%-60% are prepared respectively. An appropriate amount of reducing agent is added to the precipitant and stirred at a speed of 300-800 r / min for 10-60 min to obtain a premix. Then the oxidizing agent and the premix are simultaneously added to the first feed liquid of step (1) while stirring at a temperature of 30-50℃ and a speed of 30-200 r / min, and the pH of the system is controlled to be 2.0-5.0. The oxidizing agent is added first and the premix is added completely. A second feed liquid is obtained. The molar ratio of the oxidizing agent to the cerium source is 1.1-1.5:1, the molar ratio of the precipitant to the cerium source is 1.1-1.8:1, and the mass percentage of the reducing agent in the cerium source is 0.01%-0.2%.
[0030] (3) The premix is continuously added to the second feed liquid at a temperature of 30-50℃ and a speed of 30-200 r / min, and the pH of the system is maintained at 5.0-8.0.
[0031] (4) after the premixing solution is completely added, the system is heated to 80-100 DEG C and kept for 20-110 min, so that the reaction is completed, after the reaction is completed, the temperature is lowered to 30-50 DEG C, the reaction clear liquid in the upper layer of the reaction system is removed first, then washed with deionized water and filtered for multiple times until the conductivity of the filtrate reaches below 100 mu s / cm, the filter cake is obtained, then the filter cake is broken and dried, the drying temperature is 60-100 DEG C, the drying time is 10-30 h, and the dried pretreated material (cerium hydroxide) is obtained.
[0032] (5) the pretreated material is crushed to D50 of 5-50 mu m, and then calcined at 300-800 DEG C for 1-8 h to obtain cerium oxide polishing powder.
[0033] Another object of the present application is to provide a polishing powder prepared by the preparation method, and the specific surface area of the polishing powder is 10-60 m 2 / g.
[0034] Still another object of the present application is to provide the application of the polishing powder in the final polishing of optical glass, and the polishing powder prepared by the preparation method can effectively improve the surface quality of the optical glass after the final polishing of the optical glass, and has a long service life.
[0035] Compared with the prior art, the preparation method of the polishing powder for the final polishing of optical glass has the following advantages: the dispersing surfactant is added to the cerium nitrate solution in advance to make it fully dispersed and uniform, which is beneficial to uniform nucleation in the subsequent reaction process, and the reducing agent is added to the precipitant to prepare a premixing solution, the reducing property and the gas generation property of the reducing agent are utilized for regulation and control, the cerium oxide polishing powder with uniform particles, high specific surface area and small grains can be prepared, the polishing performance is good and the polishing life is long, the polishing powder has good advantages in the final polishing, and the polishing effect and the surface quality of the optical glass can be effectively improved. BRIEF DESCRIPTION OF DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced as follows, and obviously, the drawings in the following description can be used to obtain other drawings without creative labor by those skilled in the art.
[0037] Figure 1 It is a scanning electron microscope graph of the polishing powder prepared in the embodiment 1 of the present application;
[0038] Figure 2 It is a scanning electron microscope graph of the polishing powder prepared in the embodiment 2 of the present application;
[0039] Figure 3 Scanning electron microscope image of the polishing powder prepared in Example 3 of the present application;
[0040] Figure 4 Scanning electron microscope image of the polishing powder prepared in Example 4 of the present application;
[0041] Figure 5 Scanning electron microscope image of the polishing powder prepared in Comparative Example 1 of the present application;
[0042] Figure 6 Scanning electron microscope image of the polishing powder prepared in Comparative Example 2 of the present application;
[0043] Figure 7 Scanning electron microscope image of the polishing powder prepared in Comparative Example 3 of the present application;
[0044] Figure 8 Scanning electron microscope image of the polishing powder prepared in Comparative Example 4 of the present application;
[0045] Figure 9 Scanning electron microscope image of the polishing powder prepared in Comparative Example 5 of the present application;
[0046] Figure 10 Scanning electron microscope image of the polishing powder prepared in Comparative Example 6 of the present application. DETAILED DESCRIPTION
[0047] In order to make the technical personnel in the art better understand the technical solutions of the present application, the technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor should belong to the scope of protection of the present application.
[0048] Example 1
[0049] The present embodiment provides a preparation method of a polishing powder for optical glass final polishing and the polishing powder prepared thereby. The preparation method of the polishing powder specifically comprises the following steps:
[0050] (1) The cerium carbonate was added to a reaction kettle and a proper amount of nitric acid was added to dissolve it, to prepare a cerium nitrate solution with a concentration of 80 g / L. A proper amount of PEG2000 and PVP K30 was added to water and stirred at a speed of 950 r / min for 30 min to fully dissolve and uniformly mix the two, to obtain a dispersing surfactant. Then the dispersing surfactant was added to the cerium nitrate solution while stirring, and uniformly mixed to obtain a first feed solution. In the dispersing surfactant, the mass percentage of PEG2000 in the mass of cerium carbonate was 0.05%, and the mass percentage of PVP K30 in the mass of cerium carbonate was 0.1%.
[0051] (2) A 25% mass concentration of hydrogen peroxide, a 30 g / L concentration of ammonia water, and a 50% mass concentration of hydrazine hydrate were prepared respectively. A proper amount of hydrazine hydrate was added to the ammonia water and stirred at a speed of 500 r / min for 25 min to obtain a premix. Then the premix and hydrogen peroxide were added to the first feed solution of step (1) while stirring at a temperature of 35°C and a speed of 80 r / min, and the pH of the system was controlled at 2.5, and the hydrogen peroxide was added first to ensure that the premix was added completely. A second feed solution was obtained. The molar ratio of hydrogen peroxide to cerium carbonate was 1.2:1, the molar ratio of ammonia water to cerium carbonate was 1.1:1, and the mass percentage of hydrazine hydrate in the mass of cerium carbonate was 0.05%.
[0052] (3) The premix was added to the second feed solution at 35°C and 100 r / min, and the pH of the system was maintained at 5.0.
[0053] (4) After the premix was completely added, the system was heated to 90°C and kept for 80 min to complete the reaction. After the reaction was completed, the system was cooled to 35°C. The reaction supernatant was removed first, then washed with deionized water and filtered multiple times until the conductivity of the filtrate was below 100 μs / cm to obtain a filter cake. In this embodiment, the conductivity of the filtrate was 60 μs / cm after the filter cake was washed and filtered 6 times with deionized water. The filter cake was crushed and placed in a vacuum drying oven for drying at a temperature of 80°C for 15 h to obtain a dried pretreated material (cerium hydroxide).
[0054] (5) The pretreated material was crushed in a crusher to a D50 of 15 μm, and then calcined at 600°C for 3 h to obtain cerium oxide polishing powder. The scanning electron microscope image of the cerium oxide polishing powder prepared in this embodiment is shown in Figure 1 .
[0055] Example 2
[0056] The embodiment provides a preparation method of polishing powder for optical glass final polishing and polishing powder prepared by the method.
[0057] (1) cerium chloride is added into a reaction kettle, and a proper amount of nitric acid is added into the reaction kettle for dissolution, so that a cerium nitrate solution with a concentration of 70 g / L is prepared, a proper amount of PEG4000 and PVP K17 is added into water, and stirring is conducted at a rotating speed of 800 r / min for 45 min, so that the two are fully dissolved and uniformly mixed, and a dispersing surfactant is obtained, then the dispersing surfactant is added into the cerium nitrate solution while stirring, and uniform mixing is conducted, so that a first feed liquid is obtained; wherein the mass percentage of PEG4000 in the dispersing surfactant accounts for 0.06% of the mass of cerium carbonate, and the mass percentage of PVP K30 accounts for 0.15% of the mass of cerium carbonate.
[0058] (2) hydrogen peroxide with a mass concentration of 28%, ammonia water with a concentration of 35 g / L and hydrazine hydrate with a mass concentration of 50% are respectively prepared, a proper amount of hydrazine hydrate is added into the ammonia water, and stirring is conducted at a rotating speed of 550 r / min for 35 min, so that a premix liquid is obtained; under the condition of a temperature of 40 DEG C and a rotating speed of 80 r / min, hydrogen peroxide and the premix liquid are simultaneously added into the first feed liquid of step (1) while stirring, the pH value of the system is controlled to be 3, and the hydrogen peroxide is added first, so that a second feed liquid is obtained; wherein the molar ratio of hydrogen peroxide to cerium carbonate is 1.3:1, the molar ratio of ammonia water to cerium carbonate is 1.2:1, and the mass percentage of hydrazine hydrate accounts for 0.05% of the mass of cerium carbonate.
[0059] (3) the premix liquid is added into the second feed liquid under the condition of 40 DEG C and 100 r / min, and the pH value of the system is maintained to be 6.0.
[0060] (4) after the premix liquid is completely added, the system is heated to 85 DEG C and kept for 100 min, so that the reaction is completed, after the reaction is completed, the system is cooled to 40 DEG C, the reaction supernatant in the upper layer of the reaction system is removed, and the reaction system is washed with deionized water and filtered for multiple times, until the conductivity of the filtrate is less than 100 mu s / cm, so that a filter cake is obtained, in the embodiment, after the filter cake is washed and filtered for 8 times, the conductivity of the filtrate is measured to be 52 mu s / cm; then the filter cake is crushed and placed in a vacuum drying oven for drying, the drying temperature is 85 DEG C, and the drying time is 12 h, so that a dried pretreated material (cerium hydroxide) is obtained.
[0061] (5) the pretreated material is crushed to D50 of 10 mu m, and then calcined at 500 DEG C for 3 h, so that cerium oxide polishing powder is obtained. In the embodiment, the scanning electron microscope (SEM) image of the prepared cerium oxide polishing powder is shown in Figure 2 .
[0062] Example 3
[0063] The embodiment provides a preparation method of polishing powder for optical glass final polishing and polishing powder prepared by the method.
[0064] (1) cerium carbonate is added into a reaction kettle, and a proper amount of nitric acid is added for dissolution to prepare a cerium nitrate solution with a concentration of 20 g / L, a proper amount of PEG2000 and PVP K30 is added into water, and stirring is performed at a rotation speed of 800 r / min for 45 min to fully dissolve and uniformly mix the two to obtain a dispersing surfactant, then the dispersing surfactant is added into the cerium nitrate solution while stirring to uniformly mix to obtain a first feed liquid; wherein the mass percentage of PEG2000 in the dispersing surfactant accounts for 0.03% of the mass of the cerium carbonate, and the mass percentage of PVP K30 accounts for 0.15% of the mass of the cerium carbonate.
[0065] (2) hydrogen peroxide with a mass concentration of 25%, ammonia water with a concentration of 30 g / L and hydrazine hydrate with a mass concentration of 50% are respectively prepared, a proper amount of hydrazine hydrate is added into the ammonia water, and stirring is performed at a rotation speed of 500 r / min for 25 min to obtain a premix; under the condition of a temperature of 35 ℃ and a rotation speed of 100 r / min, hydrogen peroxide and the premix are simultaneously added into the first feed liquid of step (1) while stirring, the pH of the system is controlled to be 2.5, and the hydrogen peroxide is added first to be completely added before the premix is completely added, to obtain a second feed liquid; wherein the molar ratio of hydrogen peroxide to cerium carbonate is 1.5:1, the molar ratio of ammonia water to cerium carbonate is 1.1:1, and the mass percentage of hydrazine hydrate accounts for 0.05% of the mass of the cerium carbonate.
[0066] (3) the premix is added into the second feed liquid under the condition of 35 ℃ and 120 r / min, and the pH of the system is maintained to be 5.
[0067] (4) after the premix is completely added, the system is heated to 85 ℃ and kept for 100 min to make the reaction complete, and after the reaction is completed, the system is cooled to 35 ℃, the reaction supernatant is removed first, then the reaction system is washed with deionized water and filtered for multiple times until the conductivity of the filtrate is less than 100 μs / cm to obtain a filter cake, in the embodiment, the filter cake is crushed and placed in a vacuum drying oven after being washed and filtered with deionized water for 8 times, the conductivity of the filtrate is measured to be 70 μs / cm; then the filter cake is crushed and placed in a vacuum drying oven for drying, the drying temperature is 80 ℃, and the drying time is 15 h to obtain dried pretreated material (cerium hydroxide).
[0068] (5) the pretreated material is crushed to D50 of 15 μm, and then calcined at 600 ℃ for 3 h to obtain cerium oxide polishing powder. The scanning electron microscope image of the cerium oxide polishing powder prepared in the embodiment is shown inFigure 3 .
[0069] Example 4
[0070] (1) Cerium carbonate was added into a reaction kettle and a proper amount of nitric acid was added for dissolution to prepare a cerium nitrate solution with a concentration of 80 g / L. A proper amount of PEG2000 and PVP K30 was added into water and stirred at a speed of 950 r / min for 30 min to fully dissolve and uniformly mix the two to obtain a dispersing surfactant. Then the dispersing surfactant was added into the cerium nitrate solution while stirring to uniformly mix to obtain a first feed solution; wherein the mass percentage of PEG2000 in the dispersing surfactant to the mass of cerium carbonate was 0.05%, and the mass percentage of PVP K30 to the mass of cerium carbonate was 0.1%.
[0071] (2) Hydrogen peroxide with a mass concentration of 25%, ammonia water with a concentration of 30 g / L, and hydrazine hydrate with a mass concentration of 50% were prepared respectively. A proper amount of hydrazine hydrate was added into the ammonia water and stirred at a speed of 500 r / min for 25 min to obtain a premix. Then the premix and hydrogen peroxide were added into the first feed solution of step (1) while stirring at a temperature of 35 °C and a speed of 80 r / min, and the pH of the system was controlled at 3, and the hydrogen peroxide was added first to ensure that the premix was added completely, to obtain a second feed solution; wherein the molar ratio of hydrogen peroxide to cerium carbonate was 1.2:1, the molar ratio of ammonia water to cerium carbonate was 1.8:1, and the mass percentage of hydrazine hydrate to cerium carbonate was 0.1%.
[0072] (3) The premix was added into the second feed solution at 35 °C and 120 r / min, and the pH of the system was maintained at 6.
[0073] (4) After the premix was completely added, the system was heated to 80 °C and kept for 110 min to make the reaction complete. After the reaction was completed, the system was cooled to 35 °C. The reaction clear liquid in the upper layer was removed first, then washed with deionized water and filtered multiple times until the conductivity of the filtrate reached below 100 μs / cm to obtain a filter cake. In this embodiment, after being washed and filtered 7 times with deionized water, the conductivity of the filtrate was measured to be 60 μs / cm. Then the filter cake was crushed and placed in a vacuum drying oven for drying at a temperature of 80 °C for 15 h to obtain dried pretreated material (cerium hydroxide).
[0074] (5) The pretreated material was crushed to a D50 of 15 μm, and then calcined at 500 °C for 3 h to obtain cerium oxide polishing powder. The scanning electron microscope image of the cerium oxide polishing powder prepared in this embodiment is shown in Figure 4 .
[0075] Comparative Example 1
[0076] The example 1 is basically the same, except that no dispersing surfactant is added in step (1).
[0077] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 5 The agglomeration of the particles is more serious.
[0078] Comparative example 2
[0079] The example 1 is basically the same, except that in step (1), a proper amount of PEG2000 is stirred at a speed of 950 r / min for 30 min to fully dissolve it to obtain the dispersing surfactant, and the mass percentage of PEG2000 in the dispersing surfactant to the mass of cerium carbonate is 0.05%. That is, the dispersing surfactant in the present comparative example only contains PEG2000.
[0080] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 6 The particle size is not uniform.
[0081] Comparative example 3
[0082] The example 1 is basically the same, except that in step (1), a proper amount of PVP K30 is stirred at a speed of 950 r / min for 30 min to fully dissolve it to obtain the dispersing surfactant, and the mass percentage of PVP K30 in the dispersing surfactant to the mass of cerium carbonate is 0.1%. That is, the dispersing surfactant in the present comparative example only contains PVP K30.
[0083] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 7 The morphology of the particles is poor.
[0084] Comparative example 4
[0085] The example 1 is basically the same, except that in step (1), PEG2000 is replaced by polyacrylamide with the same added mass.
[0086] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 8 .
[0087] Comparative example 5
[0088] The example 1 is basically the same, except that in step (2), no 50% concentration of hydrazine hydrate is prepared, and no hydrazine hydrate is added to the ammonia water.
[0089] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 9 The agglomeration of the particles is more serious.
[0090] Comparative example 6
[0091] The preparation method of Example 1 is basically the same, except that Na2SO3 is used as the reducing agent in step (2) instead of hydrazine hydrate.
[0092] The scanning electron microscope image of the cerium oxide polishing powder prepared in the present comparative example is shown in Figure 1. Figure 10 .
[0093] Results and discussion
[0094] Nitrogen adsorption-desorption tests were performed on the polishing powders prepared in Examples 1 to 4 and Comparative Examples 1 to 6 to characterize the specific surface area of the polishing powders, and the test results are shown in Table 1.
[0095] Table 1: Summary of the specific surface area of the polishing powders in Examples 1 to 4 and Comparative Examples 1 to 6
[0096] Specific surface area (m 2 / g) Example 1 38.9 Example 2 36.3 Example 3 35.3 Example 4 32.1 Comparative Example 1 12.4 Comparative Example 2 15.6 Comparative Example 3 16.8 Comparative Example 4 29.2 Comparative Example 5 14.2 Comparative Example 6 18.6
[0097] To further verify the polishing performance of the polishing powders prepared in the present application, final polishing tests of optical glass were performed on all the polishing powders in Examples 1 to 4 and Comparative Examples 1 to 6, wherein the samples and instruments used in the polishing tests included: polishing powders (polishing powders prepared in Examples 1 to 4 and Comparative Examples 1 to 6, respectively), optical glass samples (blue glass, edge length 77 mm, thickness 0.29 mm), a polishing machine (model X62D9B2M-T; polishing speed: 150 rpm), a surface roughness tester (model: Surftest SV-2100; scanning mode: contact mode), an optical microscope (model: OLYMPUS BX51M, eyepiece magnification: 10x; objective lens magnification: 50x), a strong light lamp, and the test results are shown in Table 2.
[0098] The specific polishing test procedure is described as follows:
[0099] a) Each of the polishing powders in Examples 1 to 4 and Comparative Examples 1 to 6 was ball milled to a particle size distribution of D50 of 0.2-0.22 μm, and a slurry with a solid content of 10% was prepared for use.
[0100] b) A piece of blue glass was evenly cut into 10 small pieces, and the initial roughness of each small piece of blue glass was detected by a surface roughness tester to ensure that the initial roughness of the 10 pieces of blue glass was uniform, for use. If the initial roughness of an individual piece of blue glass was inconsistent with the initial roughness of the others, it was reselected until the initial roughness of the 10 pieces of blue glass was the same.
[0101] c) Polishing the blue glasses respectively using each slurry prepared in step a) on a polishing machine (polishing time is 120 min, rotation speed of the polishing machine is 50 r / min, and the pressure of the polishing machine is 60 kg), and detecting the surface roughness of each blue glass after polishing, respectively, and then observing the surface quality of each polished blue glass using an optical microscope and recording.
[0102] d) Continuing to polish each blue glass which has been polished in step c), and recording the time when the surface roughness of each blue glass after polishing is reduced by 30% compared with the initial surface roughness (when the surface roughness of the optical glass is reduced by 30% compared with that before polishing, it is generally considered that the polishing powder has reached the service life and cannot be used continuously).
[0103] Table 2: Summary of test results of the polishing powders in Examples 1 to 4 and Comparative Examples 1 to 6 in the polishing test
[0104]
[0105] The test results in Table 1 show that the specific surface areas of the polishing powder particles prepared in Examples 1 to 4 are all greater than those of the polishing powder particles prepared in Comparative Examples 1 to 6, and the polishing performance test results in Table 2 show that the polishing performance of the polishing powders prepared in Examples 1 to 4 is all obviously superior to that of the polishing powders prepared in Comparative Examples 1 to 6. Among them, the specific surface area of Comparative Example 1 without using a dispersing surfactant is the smallest, and its polishing performance is also the worst, because the particles obtained without a dispersing surfactant are prone to agglomeration, resulting in poor improvement effect of the surface roughness after polishing and low service life; and it is further illustrated that by adding a dispersing surfactant to the cerium nitrate solution in advance to make it fully dispersed and uniform, it is beneficial to uniform nucleation in the subsequent reaction process, and it is beneficial to improve the specific surface area of the prepared polishing powder particles, and thus it is helpful to improve the polishing performance of the polishing powder.
[0106] As can be seen from the comparison of Comparative Examples 2 to 4 and the examples, the effect of the dispersing surfactant prepared by using polyethylene glycol and polyvinylpyrrolidone is better than that of polyethylene glycol alone, polyvinylpyrrolidone alone, or polyethylene glycol or polyvinylpyrrolidone used together with other reagents, and the polishing performance is improved to some extent compared with Comparative Example 1, but there is still a big gap with the polishing performance of the examples, indicating that the combination of polyethylene glycol and polyvinylpyrrolidone can effectively play a synergistic effect and effectively control the growth of cerium oxide particles. Among them, the results of Comparative Example 4 in Tables 1 and 2 show that the combination of polyvinylpyrrolidone and polyacrylamide can also play a certain synergistic effect, and the effect is better than that of not using a dispersing surfactant or using only one component of the dispersing surfactant, but there is still a certain gap compared with the synergistic effect of polyethylene glycol and polyvinylpyrrolidone.
[0107] The specific surface area of the polishing powder particles prepared without using a reducing agent in Comparative Example 5 is also small, indicating that adding a reducing agent to the precipitant to prepare a premix solution and using the reducing property and the property of generating gas by decomposition of the reducing agent for regulation are conducive to the preparation of cerium oxide polishing powder with high specific surface area; the specific surface area of the polishing powder particles prepared by using Na2SO3 as a reducing agent in Comparative Example 6 is also small, although Na2SO3 is also a reducing agent, but it will not decompose to generate gas in the reaction process, resulting in that the specific surface area cannot be effectively increased. Obviously, the polishing performance of the polishing powder in Comparative Examples 5 and 6 is also poor. By combining these two comparative examples, it can be seen that by using a specific reducing agent (one or a combination of hydrazine, hydrazine hydrate or hydrazine salt), the reducing property and the property of generating gas by decomposition are used for regulation, which is more conducive to obtaining cerium oxide polishing powder with high specific surface area and small grains, and helps to improve the polishing performance.
[0108] The purpose of the present application is to provide a method for preparing cerium oxide polishing powder with high specific surface area and small grains, by adding a dispersing surfactant to the cerium nitrate solution in advance to make it fully dispersed and uniform, which is conducive to uniform nucleation in the subsequent reaction process; and a reducing agent is added to the precipitant in advance to prepare a premix solution, and then an oxidizing agent and the premix solution are added to the uniformly dispersed cerium nitrate solution at the same time, and the addition speed is controlled to ensure that the oxidizing agent is added first and the premix solution is added completely, and in the reaction process, the reducing property and the property of generating gas by decomposition of the reducing agent are used for regulation, so that cerium oxide polishing powder with uniform particles, high specific surface area and small grains can be prepared. By using the preparation method of the present application, cerium oxide with a specific surface area of 10-60 m 2 / g, uniform particles, polyhedral morphology and small grains with edges and corners can be prepared, which is applied to the final polishing of optical glass, and exhibits good polishing performance and long polishing life, which can effectively improve the polishing effect and surface quality of optical glass.
[0109] The above embodiments are only for illustrating the technical concept and characteristics of the present application, and the purpose is to enable those skilled in the art to understand the content of the present application and to implement it, and cannot limit the protection scope of the present application. Any equivalent changes or modifications made according to the spirit and essence of the present application shall be covered within the protection scope of the present application.
Claims
1. A method for producing a polishing powder for final polishing of optical glass, characterized by, The method comprises the following steps: adding a dispersing surfactant into the cerium nitrate solution, stirring uniformly to obtain a first liquid; the dispersing surfactant is obtained by mixing polyethylene glycol and polyvinylpyrrolidone; preparing a premix, adding an oxidizing agent and the premix into the first liquid at a first temperature simultaneously, maintaining the pH value of the system at 2.0-5.0, and ensuring that the oxidizing agent is added first, to obtain a second liquid; the premix is a mixture of a precipitant and a reducing agent; continuing to add the premix into the second liquid at the first temperature, and maintaining the pH value of the system at 5.0-8.0; after the premix is added completely, increasing the temperature to a second temperature and keeping the temperature, reacting, decreasing the temperature to the first temperature after the reaction is completed, and then filtering and drying to obtain a pretreated material; crushing the pretreated material to D50 of 5-50 μm, and then calcining to obtain the polishing powder.
2. The production method according to claim 1, characterized by, The concentration of the cerium nitrate solution is 20-120 g / L, and the cerium nitrate solution is prepared from a cerium source and nitric acid, wherein the cerium source is a combination of one or more of cerium carbonate or cerium chloride.
3. The preparation method according to claim 2, characterized in that, The mass ratio of polyethylene glycol to polyvinylpyrrolidone in the dispersing surfactant is 1:1-5.
4. The preparation method according to claim 2, characterized in that, The mass percentage of the dispersing surfactant in the first liquid to the mass of the cerium source is 0.01-0.5%.
5. The preparation method according to claim 2, characterized in that, The method for preparing the premix is: first, preparing a precipitant with a concentration of 5-40 g / L, then adding a reducing agent into the precipitant, and stirring at a speed of 300-800 r / min for 10-30 min.
6. The preparation method according to claim 5, characterized in that, The mass concentration of the reducing agent is 40%-60%, and the mass percentage of the reducing agent to the mass of the cerium source is 0.01%-0.2%.
7. The preparation method according to claim 6, characterized in that, The reducing agent is a combination of one or more of hydrazine, hydrazine hydrate or hydrazine salt.
8. The preparation method according to claim 5, characterized in that, The molar ratio of the precipitant to the cerium source is 1.1-1.8:
1.
9. The preparation method according to claim 2, characterized in that, The mass concentration of the oxidizing agent is 15%-35%, and the molar ratio of the oxidizing agent to the cerium source is 1.1-1.5:
1.
10. The method of claim 1, wherein, The first temperature is 30-50 ℃, and the second temperature is 80-100 ℃.
11. The method of claim 1, wherein, After the temperature is decreased to the first temperature after the reaction is completed, the upper reaction clear liquid in the reaction system is removed before filtering; during the filtering process, the filter cake is washed with water for multiple times, and the conductivity of the filtrate is tested after each washing until the conductivity of the filtrate is below 100 μs / cm, to obtain the filter cake.
12. The method of claim 11, wherein, Before the step of drying, the filter cake obtained by filtering is crushed and then dried, and the drying temperature is 60-100 ℃, and the drying time is 10-30 h.
13. The method of claim 1, wherein, During the process of adding the oxidizing agent and the premix into the first liquid at the first temperature simultaneously, the oxidizing agent and the premix are added into the first liquid while stirring, and the stirring speed is 30-200 r / min.
14. The method of claim 1, wherein, During the process of increasing the temperature to the second temperature and keeping the temperature after the premix is added completely, the keeping time is 20-100 min.
15. The method of claim 1, wherein, The calcining temperature is 300-800 ℃, and the calcining time is 1-8 h.
16. A polishing powder, characterized by The polishing powder produced by the production method according to any one of claims 1 to 15 has a specific surface area of 10 to 60 m 2 / g.
17. Use of a polishing powder according to claim 16 for the final polishing of optical glass.